Deformation Mechanism and Surrounding Rock Control in High-Stress Soft Rock Roadway: A Case Study. (25th August 2021) - Gao, Yuwen; Wang, Chen; Liu, Yong; Wang, Yuyang; Han, Lianchang
Abstract : Stability control for soft and broken surrounding rock of roadways is one important segment of mining support. Taking 1412 Roadway of a mine in Guizhou province as a research background, this paper studies the large deformation of surrounding rock and the failure of bolts and cables. The deformation and failure mechanism are analyzed by related theoretical analysis and field survey. Then, the feasibility of the composite controlling scheme, bolts and cables + grouting + steel tube concrete support, is verified by theoretical analysis, numerical simulation, and industrial test. Following results can be obtained: main reasons leading to the deformation of surrounding rock and the failure of cables and blots in the roadway are low strength and poor self-stability of surrounding rock, complex stress environment, low support resistance, and lack of reinforced support in crucial supporting sites; the control scheme can reduce the surrounding rock deformation by 40%, which meets the requirements of field application so that this practice can provide some guidance for other similar projects.